Synaptic enrichment and dynamic regulation of the two opposing dopamine receptors within the same neurons - Shun Hiramatsu; Kokoro Saito; Shu Kondo; Hidetaka Katow; Nobuhiro Yamagata; Chun-Fang Wu; Hiromu Tanimoto (eLife)
Dopamine can play opposing physiological roles depending on the receptor subtype. In the fruit fly Drosophila melanogaster, Dop1R1 and Dop2R encode the D1- and D2-like receptors, respectively, and are reported to oppositely regulate intracellular cAMP levels. Here, we profiled the expression and subcellular localization of endogenous Dop1R1 and Dop2R in specific cell types in the mushroom body circuit. For cell-type-specific visualization of endogenous proteins, we employed reconstitution of split-GFP tagged to the receptor proteins. We detected dopamine receptors at both presynaptic and postsynaptic sites in multiple cell types. Quantitative analysis revealed enrichment of both receptors at the presynaptic sites, with Dop2R showing a greater degree of localization than Dop1R1. The presynaptic localization of Dop1R1 and Dop2R in dopamine neurons suggests dual feedback regulation as autoreceptors. Furthermore, we discovered a starvation-dependent, bidirectional modulation of the presynaptic receptor expression in the protocerebral anterior medial (PAM) and posterior lateral 1 (PPL1) clusters, two distinct subsets of dopamine neurons, suggesting their roles in regulating appetitive behaviors. Our results highlight the significance of the co-expression of the two opposing dopamine receptors in the spatial and conditional regulation of dopamine responses in neurons.